Long-term follow up after endoscopic valve therapy in patients with severe emphysema. (July 2019) - Gompelmann, Daniela; Heinhold, Tobias; Rötting, Matthias; Bischoff, Elena; Kontogianni, Konstantina; Eberhardt, Ralf; Herth, Felix J. F.
Background and objective: Endoscopic valve therapy is a treatment modality in patients with advanced emphysema and absent interlobar collateral ventilation (CV). So far, long-term outcome following valve implantation has been insufficiently evaluated. The aim of this study was to investigate the real-world efficacy of this interventional therapy over 3 years. Methods: From 2006 to 2013, 256 patients with severe emphysema in whom absent CV was confirmed underwent valve therapy. The 3-year effectiveness was evaluated by pulmonary function testing (VC, FEV1, RV, TLC), 6-minute-walk test (6-MWT) and dyspnea questionnaire (mMRC). Long-term outcome was also assessed according to the radiological outcome following valve placement. Results: Of 256 patients treated with valves, 220, 200, 187, 100 and 66 patients completed the 3-month, 6-month, 1-year, 2-year and 3-year follow-up (FU) visit, respectively. All lung function parameters, 6-MWT and mMRC were significantly improved at 3- and 6-month FU. At 1-year FU, patients still experienced a significant improvement of all outcome parameters expect VC (L) and TLC (%). At 2 years, RV (L and %) and TLC (L and %) remained significantly improved compared to baseline. Three years after valve therapy, sustained significant improvement in mMRC was observed and the proportion of patients achieving a minimal clinically important difference from baseline in RV and 6-MWT was still 71% and 46%, respectively. Overall, patients with complete lobar atelectasis exhibited superior treatment outcome with 3-year responder rates to FEV1, RV and 6-MWT of 10%, 79% and 53%, respectively. Conclusions: Patients treated by valves experienced clinical improvement over 1 year following valve therapy. Afterwards, clinical benefit gradually declines more likely due to COPD progression. The reviews of this paper are available via the supplemental material section.